Pathophysiological significance of the two-pore domain K+ channel K2P5.1 in splenic CD4+CD25− T cell subset from a chemically-induced murine inflammatory bowel disease model - Nakakura, Sawa; Matsui, Miki; Sato, Aya; Ishii, Mizuki; Endo, Kyoko; Muragishi, Sayaka; Murase, Miki; Kito, Hiroaki; Niguma, Hiroki; Kurokawa, Natsumi; Fujii, Masanori; Araki, Masatake; et al. (Frontiers in Physiology, 2015)
The alkaline pH-activated, two-pore domain K+ channel K2P5.1 (also known as TASK2/KCNK5) plays an important role in maintaining the resting membrane potential, and contributes to the control of Ca2+ signaling in several types of cells. Recent studies highlighted the potential role of the K2P5.1 K+ channel in the pathogenesis of autoimmune diseases such as rheumatoid arthritis and multiple sclerosis. The aim of the present study was to elucidate the pathological significance of the K2P5.1 K+ channel in inflammatory bowel disease (IBD). The degrees of colitis, colonic epithelial damage, and colonic inflammation were quantified in the dextran sulfate sodium-induced mouse IBD model by macroscopic and histological scoring systems. The expression and functional activity of K2P5.1 in splenic CD4+ T cells were measured using real-time PCR, Western blot, and fluorescence imaging assays. A significant increase was observed in the expression of K2P5.1 in the splenic CD4+ T cells of the IBD model. Concomitant with this increase, the hyperpolarization response induced by extracellular alkaline pH was significantly larger in the IBD model with the corresponding intracellular Ca2+ rises. The expression of K2P5.1 was higher in CD4+CD25- T cells than in CD4+CD25+ regulatory T cells. The knockout of K2P5.1 in mice significantly suppressed the disease responses implicated in the IBD model. Alternations in intracellular Ca2+ signaling following the dysregulated expression of K2P5.1 were associated with the disease pathogenesis of IBD. The results of the present study suggest that the K2P5.1 K+ channel in CD4+CD25- T cell subset is a potential therapeutic target and biomarker for IBD.